Analisis Risiko Kerja pada PT. Indoclean Dynamic - Kellyn F Carolline; Winlie Chang; Handi Wilujeng Nugroho (Scientific Literacy Innovation and Technology Journal, 2024)
The importance of occupational safety and health (K3) in industry, especially in Indonesia which is experiencing rapid growth in various sectors, including industrial chemistry. The use of chemicals and modern equipment in the industrial chemical production process increases the potential for danger to occupational health and safety and the environment. Indoclean Dynamic Company is a chemical industry company in Indonesia, using risk analysis, various potential hazards were identified, such as dust, inadequate ventilation, use of equipment without personal protection (PPE), and cramped work space conditions. Risk assessment is carried out to determine the level of risk which includes the possibility of occurrence and the level of severity that can be caused. The assessment results show that several processes have high risks, especially related to the use of PPE and room lighting. Suggested prevention suggestions include providing appropriate PPE, improving room lighting, and warning signs of dangerous chemicals. In conclusion, risk prevention and control efforts need to be improved to ensure a safe and comfortable work environment for PT.Dynamic Indoclean employees.